The Use of Fecal Microbiome Transplant in Treating Human Diseases: Too Early for Poop? - Ser, Hooi-Leng; Letchumanan, Vengadesh; Goh, Bey-Hing; Wong, Sunny Hei; Lee, Learn-Han (Frontiers in Microbiology, 2021)
Faecal microbiome transplant (FMT) has gained popularity over the past few years, given its success in treating several gastrointestinal diseases. At the same time, microbial populations in the gut have been shown to have more physiological effects than we expected as “habitants” of the gut. The imbalance in the gut microbiome or dysbiosis, particularly when there are excessive harmful pathogens, can trigger not just infections but can also result in the development of common diseases, such as cancer and cardiometabolic diseases. By using FMT technology, the dysbiosis of the gut microbiome in patients can be resolved by administration of faecal materials from a healthy donor. The current review summarizes the history and current uses of FMT before suggesting potential ideas for its high-quality application in clinical settings.